Blockchain technology in healthcare: A PRISMA-guided systematic review of implementation barriers, trust, literacy and institutional readiness - Lins, B.; Sousa, M. J.; Correia, R.; Rocha, Á. (Informatica, 2025)
Blockchain technology is transforming the healthcare sector by addressing challenges such as data security and interoperability. This systematic literature review, conducted using the PRISMA 2020 methodology, synthesises findings from 25 peer-reviewed studies to examine the applications, challenges, and future directions of blockchain in healthcare. Results reveal that most studies are theoretical or review-based, followed by case studies, with a small proportion of experimental research. This distribution highlights the early stage of blockchain research in healthcare and emphasises the need for empirical and experimental investigations. By synthesising findings, this study provides an overview of the current state of art regarding blockchain in healthcare.